Smart poster for information delivery services using Near Field Communication (NFC) / Zawawi Ismail@ Abdul Wahab and Norfazilah Ibrahim - Ismail@ Abdul Wahab, Zawawi; Ibrahim, Norfazilah (2016)
Currently, the traditional posters have been used as the platform for advertising and transmission of information. Typically, traditional posters not only contain elements of texts but also images in order to attract the attention of people. From an initial study conducted, it is found that texts and images have an impact on the effectiveness of information delivery especially for those hectic and less-creativity people. People are now demand for richer contents such as audio and video especially those who own smartphones. Therefore, Smart Poster for Information Delivery Services Using Near Field Communication is proposed through a combination of smartphones and NFC technology. A smart poster will act like the traditional poster, but with wealthier elements such as text, image, audio, and video. This application allows the user to create and retrieve contents of the smart posters, and is developed by adapting RAD model which involved preliminary study, system analysis, system design, system development, system testing and evaluation, and documentation. Results from the analysis indicate that the application has satisfied the respondents in terms of usability (mean = 3.80; SD = 0.42), interface design (mean = 3.80; SD = 0.67), functionality (mean = 4.10; SD = 0.74) and content (mean = 3.30; SD = 0.48) of the application. The dispersion of standard deviation is rather small that is less than one for all categories. This indicates the insignificant difference in the respondents’ satisfactory level.